The Effect of Memorizing the Quran on Academic Achievement of Students at Hidayatul Qur'an Islamic High School - Nurhayati, Fitri; Rahman, Priyanggo Karunia; Hasan, Subri (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study explores the influence of Quranic memorization on the academic achievement of twelfth-grade students at Madrasah Aliyah Swasta Hidayatul Qur’an, Puding Besar. Using an associative quantitative approach with simple linear regression analysis, data were collected through questionnaires, observations, and documentation of semester grades. The findings indicate a significant positive relationship between the intensity of Quranic memorization and students’ academic performance, with a contribution rate of 40%. Statistical analysis shows that the calculated t-value (4.758) exceeds the critical value (2.034), supporting the acceptance of the alternative hypothesis. These results suggest that Quranic memorization is a key factor in enhancing academic achievement. The study offers practical recommendations for Islamic educational institutions to strengthen tahfidz programs as an integral part of the formal curriculum.